Rhizosphere microbiome metagenomics in PGPR-mediated alleviation of combined stress from polypropylene microplastics and Cd in hybrid Pennisetum - Zhao, Si-Yu; Meng, Yue-Liang; Yang, Zi-Han; Li, B. Larry; Li, Yu-Ying; Han, Hui; Liu, Ling; Duan, Peng-Fei; Chen, Zhao-Jin (Frontiers in Microbiology, 2025)
The simultaneous presence of microplastics (MPs) and heavy metals in soil may result in heightened toxicity, causing more significant adverse effects on plant growth. Plant growth-promoting rhizobacteria (PGPR) have demonstrated significant capacities in alleviating the toxic stress caused by the combined pollution of heavy metals and other contaminants. However, research on the impacts and processes of PGPR in alleviating stress induced by the combined pollution from MPs and heavy metals is still insufficient. This study involved a pot experiment to evaluate the ability of PGPR to mitigate stress induced by the combined pollution from polypropylene microplastic (PP MPs) particles of different sizes (6.5 μm and 830 μm) and the heavy metal cadmium (Cd) in the bioenergy plant hybrid Pennisetum. Moreover, metagenomic analysis was used to examine the effects of PGPR on the rhizospheric microbial community and function. The cocontamination of PP and Cd affected the growth of the hybrid Pennisetum differently depending on the size of the MPs particles, with the aboveground and underground lengths of the 6.5 μm PP + Cd experimental group being smaller than those of the 830 μm PP + Cd group. The PGPRs (Bacillus sp. Y-35, Bacillus sp. Y-62, Bacillus sp. Y-S, and Enterobacter sp. Y-V) successfully alleviated the stress caused by the combined pollution of PP and Cd, resulting in increases of 8.24 and 42.21% in the plant height and dry weight, respectively. The metagenomic studies indicated that the cocontamination of PP and Cd, along with PGPR inoculation, altered the composition of the rhizospheric bacterial community, leading to changes in microbial diversity indices and the composition of dominant groups such as Pseudomonadota, Actinomycetota, and Acidobacteriota. The functional analysis revealed that the main functional groups involved glucose metabolism, energy metabolism, signal transduction, and nucleotide metabolism. The MPs particle size and different PGPR significantly affected functions such as the pentose phosphate pathway, benzoate degradation, and amide biosynthesis. This study provides essential data and scientific evidence on the ecotoxicological effects of simultaneous contamination by MPs and heavy metals, as well as insights into potential bioremediation methods.